DEVELOPMENT ISSUES IN ALGORITHMS FOR SYSTEM LEVEL SELF-DIAGNOSIS - Mashkov, Victor; Smolarz, Andrzej; Lytvynenko, Volodymyr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The paper deals with the problem of developing probabilistic algorithm for system level self-diagnosis. The main goal of the suggested algorithm is to minimize the mean time of its executing. The algorithm is based on the computing of the posterior probability of fault-free state of each system unit. Final decision about unit’s state is made on the chosen decision rule. The execution of the probabilistic algorithm is elucidated with the help of simple example and then explained for the case of more complex systems.